Analisa Foto Makro Dan Sem Pada Komposit Ebonit Dengan Penguat Serat Rami Untuk Pengembangan Komponen Otomotif - Nugrahanto, Fajar Agung, Joko Sedyono, ST., M.Eng., Ph.D (2016)
This study aims Knowing the results of the macro image on the variation of fiber 20 phr and 40 phr and calculating the void area on the SEM images on a variety of hemp fiber weight 20 phr and 40 phr. The manufacture of composite materials are flax fibers as reinforcement and rubber ebonite as matriknya , the result of the fracture of composite ebonite analyzed by the macro image to see the fault that occurred and testing SEM photograph to see voids in the composite ebonite with magnification 5000x. The results were obtained based on the analysis of the macro image fault is the fault of clay . That has a fracture uneven , fiber appears out ( fiber pull out) or filamentous which makes its price steeper. At 20 phr variation flax fibers are void area of 231.695 mm2 with 5000x magnification , In this variation there is a side section void almost evenly between the particles . The cause of void on the variation is caused by the influence of particles or elements less homogenous material . Thus causing voids. Whereas in hemp fibers 40 phr variations are void of 193.605 mm2 with 5000x magnification . The occurrence of void in this variation is so small because at this variation parikelnya bond together with fiber.